Nuclear Waste Management and Disposal: A Critical Examination of Nuclear Waste Management and Disposal (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Nuclear waste or regularly known as radioactive waste is a major issue. It has very hazard impacts on human being and environment. The primary target of this paper is to review the management and disposal of the nuclear waste.